Detection of cellulolytic bacteria from the human colon - Kopecný, J; Hajer, J; Mrázek, J (Folia microbiologica, 2004)
The main representatives of bacteria in the human colon were investigated by specific PCR and denaturing gradient gel electrophoresis (DGGE). Prevalent in both cases were species of Bifidobacterium, Clostridium, Bacteroides, Faecalibacterium and Eubacterium. Simultaneously, cellulolytic bacteria were isolated from the human feces. The largest proportion was represented by ruminococcus-like isolates. Their presence was confirmed both by PCR and DGGE methods; the latter one was able to give more comprehensive data about the composition of bacterial population in the human colon chyme.
Keywords: Electrophoresis, Polyacrylamide Gel; kolon; DNA bakterií; geny rRNA; Humans; elektroforéza v polyakrylamidovém gelu; DNA, Ribosomal; DNA fingerprinting; celulosa; Ruminococcus; Genes, rRNA; DNA Fingerprinting; RNA ribozomální 16S; Colon; lidé; Bacteroides; Clostridium; RNA, Ribosomal, 16S; DNA, Bacterial; Eubacterium; Cellulose; celulasa; polymerázová řetězová reakce; Polymerase Chain Reaction; ribozomální DNA; Bacteria; Bifidobacterium; Cellulase